Among System from Ki Hajar Dewantara’s Teaching: Building a Responsive Attitude of Students in Following Online Learning - Maharani, Friskilia; Soesanto, Robert Harry (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
This research aims to uncover the role of teachers in efforts to build a responsive attitude of students by using the Among system from the teaching of Ki Hajar Dewantara in online learning. This research method uses descriptive methods with a qualitative approach. The subjects in this study were students of class XI MIPA 2 which consisted of 34 students. Data collection techniques are class observation, RPP, and reflection. This research data analysis technique uses qualitative descriptive analysis by describing each phase of the system among mathematical learning in relation to students’ responsive attitude. The results of this study show that the among system is able to build a student's responsive attitude that is seen through increasing student awareness of their duties and responsibilities and active involvement in the classroom as measured through students asking questions, answering, arguing in discussions, entering classes, and doing tasks on time. This result is due to the implementation of phases in learning, namely the planning phase, the independent atmospheric phase, the among phase, the accountability phase, and the closing phase. In each phase there is a concept that is 3N, the principle of independence and family to the guidelines that are the role of teachers in the educational trilogy. In this educational trilogy, the teacher plays as: Ing ngarsa sung tuladha, Ing madya mangun karsa, and Tut wuri handayani.